2015
DOI: 10.1093/gerona/glv008
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-Induced Oxidative Stress Causes Endothelial Dysfunction

Abstract: Age is a risk factor for cardiovascular disease, suggesting a causal relationship between age-related changes and vascular damage. Endothelial dysfunction is an early pathophysiological hallmark in the development of cardiovascular disease. Senescence, the cellular equivalent of aging, was proposed to be involved in endothelial dysfunction, but functional data showing a causal relationship are missing.Endothelium-dependent vasodilation was measured in aortic rings ex vivo. We investigated aortas from aged C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 57 publications
0
69
0
Order By: Relevance
“…Therefore, it may have value as a biomarker, but it is difficult to conclude that shorter telomeres in leukocytes directly contribute to vascular aging or CVD. Still, in mice, the accumulation of critically short telomeres in vascular tissue resulting from telomerase deficiency is sufficient to induce endothelial dysfunction, whereas ectopic expression of telomerase in human VSMCs both lengthens telomeres and increases plaque stability via greater cap stability and a normalized VSMC phenotype in atherosclerosis . Still, TERT not only extends the telomere, but also regulates eNOS expression in human microvessels at translational and posttranslational levels as well as prevents oxidative stress via reduced mitochondrial ROS and improved endothelial function .…”
Section: Telomere Dysfunction: An Initial Step For Vascular Agingmentioning
confidence: 99%
“…Therefore, it may have value as a biomarker, but it is difficult to conclude that shorter telomeres in leukocytes directly contribute to vascular aging or CVD. Still, in mice, the accumulation of critically short telomeres in vascular tissue resulting from telomerase deficiency is sufficient to induce endothelial dysfunction, whereas ectopic expression of telomerase in human VSMCs both lengthens telomeres and increases plaque stability via greater cap stability and a normalized VSMC phenotype in atherosclerosis . Still, TERT not only extends the telomere, but also regulates eNOS expression in human microvessels at translational and posttranslational levels as well as prevents oxidative stress via reduced mitochondrial ROS and improved endothelial function .…”
Section: Telomere Dysfunction: An Initial Step For Vascular Agingmentioning
confidence: 99%
“…Atrial endothelial senescence was found to promote thrombus formation and extracellular matrix remodeling (3). In an aging mouse model with vascular endothelium damage, antioxidant therapy can alleviated the dysfunction of aging vascular endothelium cells (4). Studies have shown that long-term addition of the antioxidant vitamin C (VC), which can reduce the immune levels associated with thymic aging (5).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cellular senescence is characterized by shortened telomere length or reduced telomerase activity . Oxidative stress and inflammation have been implicated in the ageing process and adversely affect endothelial availability and function . Oxidative stress compromises telomere integrity and nitric oxide (NO) bioavailability to accelerate cellular senescence in endothelial cells .…”
Section: Introductionmentioning
confidence: 99%